Long‐term avian community response to housing development at the boundary of US protected areas: effect size increases with time. Issue 5 (23rd July 2015) - Wood, Eric M.; Pidgeon, Anna M.; Radeloff, Volker C.; Helmers, David P.; Culbert, Patrick D.; Keuler, Nicholas S.; Flather, Curtis H.
Summary: Biodiversity conservation is a primary function of protected areas. However, protected areas also attract people, and therefore, land use has intensified at the boundaries of these lands globally. In the USA, since the 1970s, housing growth at the boundaries (<1 km) of protected areas has increased at a rate far higher than on more distant private lands. Here, we designed our analyses to address our central hypothesis that increasing housing density in and near protected areas will increasingly alter their avian communities. We quantified the relationship between abundance and richness of protected‐area avian species of greatest conservation need, land‐cover affiliates (e.g. species associated with natural land cover such as forest breeders) and synanthropes (e.g. species associated with humans) with housing density on the boundary of protected areas and on more distant private lands from 1970 to 2010 in three ecoregions of the USA. We accomplished this using linear mixed‐model analyses, data from the US Census Bureau and 90 routes of the North American Breeding Bird Survey. Housing density at the boundary of protected areas tended to be strongly negatively related with the abundance and richness of species of greatest conservation need and land‐cover affiliates (upwards of 88% of variance explained) and strongly positively related with synanthropes (upwards of 83% of variance explained). The effect size of these relationships increased in most cases from 1970 to 2010 and was greatest in the densely developed eastern forests. In the more sparsely populated West, we found similar, though weaker, associations. Housing density on private lands more distant from protected areas had similar, but more muted negative effects. Synthesis and applications . Our results illustrate that as housing density has increased along the boundary of protected areas, the conservation benefit of these lands has likely diminished. We urge conservation planners to prioritize the purchase of private‐land inholdings in order to maximize the extent of unfragmented natural lands within protected areas. Further, we strongly recommend that land‐use planners implement boundary management strategies to alter the pattern of human access to protected areas, cluster development to concentrate the footprint of rural housing, and establish conservation agreements through local land trusts to buffer protected areas from the effects of development along protected‐area boundaries. To maximize the conservation benefit of protected areas, we suggest that housing development should be restricted within 1 km of their boundaries. Abstract : Our results illustrate that as housing density has increased along the boundary of protected areas, the conservation benefit of these lands has likely diminished. We urge conservation planners to prioritize the purchase of private‐land inholdings in order to maximize the extent of unfragmented natural lands within protected areas. Further, we strongly recommend that land‐use planners implement boundary management strategies to alter the pattern of human access to protected areas, cluster development to concentrate the footprint of rural housing, and establish conservation agreements through local land trusts to buffer protected areas from the effects of development along protected‐area boundaries. To maximize the conservation benefit of protected areas, we suggest that housing development should be restricted within 1 km of their boundaries.